Mistletoe Christmas : an anthology - James, Eloisa; Caldwell, Christi; Ridley, Erica; MacGregor, Janna (AvonBooks, an imprint of HarperCollins Publishers, 2021)
The Duke of Greystoke's Christmas Revelry is famous throughout the British Isles for its plays, dancing, magical grotto, not to mention scandals. Lady Cressida, the duke's daughter, is too busy managing the entertainments, and besides, her own father has called her dowdy. Her cousin, Lady Isabelle Wilkshire, is directing Cinderella and has no interest in marriage. Lady Caroline Whitmore is already (unhappily) married; the fact that she and her estranged husband have to pretend to be together just makes her dread the party all the more. But not as much as Miss Louisa Harcourt, whose mother bluntly tells her that this is her last chance to escape the horrors of being an old maid. A house party so large that mothers lose track of their charges leads to a delightful, seductive quartet of stories.